La bande dessinée Congo 50 ou la mémoire collective d’une indépendance difficile - Sandra Federici (Continents manuscrits)
In the comic book Congo 50, issued in 2010 by Roularta Books and Africalia to celebrate the fiftieth anniversary of the Independence of Congo, eight comic artists of the association BD Kin Label tell the history of the 50 years of independence of their country, under the supervision of the French scriptwriter Alain Brezault and the art direction of Congolese comic author Asimba Bathy. The development of ideas and the process of creating the album are digitally archived, and are based on the research of balance between the roles and the workloads of the various project contributors. This collaborative publication could be considered as a typical example of the artwork produced by African comic authors in that cultural products often come from the “South” due to the solicitation of institutional commands from the “North”.